Mozambique - The Second Roads and Coastal Shipping Project - World Bank (Washington, DC, 2012)
The project was estimated to cost a total of $814.6 million - the IDA Credit was for the equivalent of $188 million - and it was implemented by the government over the period 1994-2001. The co-financiers included the African Development Bank, the European Union, USAID, Caisse Francaise de Developpment/Republic of South Africa, Arab Bank Economic Development, the Kuwait Fund, KfW, donors for the Feeder Roads program and Phase II donors. The objectives of the project were to (i) contribute to the restoration of economic growth through improving road transport and protecting selected past road investments by rehabilitating priority roads, undertaking backlogged periodic maintenance, and resuming regular maintenance of the paved and unpaved networks; and (ii) further strengthening the capacity of the road sector to ensure effective planning and monitoring by the government, and the development of private sector contractors and operations.